2020
DOI: 10.1111/cfs.12781
|View full text |Cite
|
Sign up to set email alerts
|

Influences on children's voices in family support services: Practitioner perspectives

Abstract: Australia's 2017 Royal Commission into Institutional Responses to Child Sexual Abuse recommended to organizations that children should participate in decisions affecting their lives as a safety standard. While a substantial body of research about children's voices in statutory or out-of-home care now exists, there remains a paucity of research into children's voices in family support services delivered by nongovernment organizations. This is despite the primary service purpose being to benefit children. This l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 29 publications
4
22
0
Order By: Relevance
“…Practitioners, who work directly with children and families highlighted the characteristics of children and families as facilitators, particularly those who have good communication skills which allow them to express themselves more easily. This is in line with previous research where communicating with children has been described as one of the challenges of participation (Kosher and Ben-Arieh, 2019); achieving this principle in practice is not easy (Harkin et al , 2020).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Practitioners, who work directly with children and families highlighted the characteristics of children and families as facilitators, particularly those who have good communication skills which allow them to express themselves more easily. This is in line with previous research where communicating with children has been described as one of the challenges of participation (Kosher and Ben-Arieh, 2019); achieving this principle in practice is not easy (Harkin et al , 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Some managers had contradictory views, as some perceived there is a lack of organisational structures, resources and time for practitioners to engage in participatory practice, whereas others had mentioned these as facilitators. These limitations, however, echo the findings of previous studies where limited resources have been identified as a barrier for participation particularly where the lack of resources prevents practitioners from turning children’s feelings and wishes into reality (Harkin et al , 2020; Kirz and Skiveness, 2017). Effort and time is needed to embed participation (Fudge et al , 2008; Harkin et al , 2020; Hogg and Williamson, 2001; Hogg, 2007; Zakus and Lysack, 1998), and this study has borne this out.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This resulted in the development of Project 1 (in 2018-2020) that sought understanding of the everyday experiences of their frontline practitioners (Phase 1) and children 6-17 years of age whose families received family support services from the UnitingCare NGO (Phase 2); and the subsequent Project 2 (in 2019-2021) that developed critical reflection workshops with management and staff to help transform practice. Prior to this research, an online baseline survey of practitioners' attitudes and assumptions toward children's participation in practice was conducted (Harkin et al, 2020). The survey received 55 respondents (50% response rate) from the organisation's family support practitioners (social workers and colleagues) and included qualitative and quantitative findings that informed Phase 1 of this research.…”
mentioning
confidence: 99%